REVIEW: VARIOUS TREATMENTS NAOH, SEA WATER, FUMIGATION, LIQUID SMOKE TO IMPROVE TENSILE STRENGTH AND SURFACE MORPHOLOGY OF NATURAL FIBER - Muslimin, Mukhlis; Wirawan, Willy Artha; Palungan, Musa Bondaris (Jurnal Rekayasa Mesin, 2024)
This article is a literature review of several studies oriented toward the treatment of natural fiber to improve the surface morphology and tensile strength of the fiber. The method used is to review several studies that describe the physical and mechanical properties of natural fiber with different treatments such as immersion of sago fiber in liquid smoke, coconut fiber in NaOH, palm fiber in seawater, and smoking of king pineapple fiber, and banana stem fiber with liquid smoke. The results of the review showed that the treatment was able to increase the tensile strength of sago fiber by 26.77%, coconut fiber by 81.25%, palm fiber by 67.40%, waru bark fiber by 59,97%, coconut fiber with limestone water 34,96 %, king pineapple fiber by 74.45%, and banana stem fiber by 43.78%. The effect of some of these treatments can also change the morphology of the fiber. So, it was concluded that treatment was needed to change the physical properties of the fiber in the form of morphology and mechanical properties in the form of better fiber tensile strength so that the fiber used as a composite reinforcement could improve the mechanical properties of the composite.